2016
DOI: 10.1016/j.dark.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Hořava Gravity in the Effective Field Theory formalism: From cosmology to observational constraints

Abstract: We consider Hořava gravity within the framework of the effective field theory (EFT) of dark energy and modified gravity. We work out a complete mapping of the theory into the EFT language for an action including all the operators which are relevant for linear perturbations with up to sixth order spatial derivatives. We then employ an updated version of the EFTCAMB/EFTCosmoMC package to study the cosmology of the low-energy limit of Hořava gravity and place constraints on its parameters using several cosmologic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 161 publications
2
84
0
Order By: Relevance
“…[12], while the remaining operators have been introduced by some of the authors of this paper in Ref. [41], where it is shown that they are necessary to map the high-energy Hořava gravity action [71] in the EFT formalism.…”
Section: (1 + ω(T))r + λ(T) − C(t)δgmentioning
confidence: 99%
“…[12], while the remaining operators have been introduced by some of the authors of this paper in Ref. [41], where it is shown that they are necessary to map the high-energy Hořava gravity action [71] in the EFT formalism.…”
Section: (1 + ω(T))r + λ(T) − C(t)δgmentioning
confidence: 99%
“…Among cosmologists, it isn't unfamiliar that, in inflationary Universe an ad hoc EoS for dark energy can be ruled out [26,27]. But for late time cosmology where HLG is conjectured to reduce to Einstein's GRG, evidences for dark energy appear.…”
Section: Reminder To Horava-lifshitz Gravitymentioning
confidence: 99%
“…The EFT approach preserves a direct link with those theories of modified gravity which show one extra scalar DoF and they can be fully mapped in the EFT language [11][12][13]19,20,26]. Then, by using the mapping with specific theories and the solution in the dS limit for the chosen theories, we can deduce the behavior of the EFT functions.…”
Section: The De Sitter Limitmentioning
confidence: 99%
“…For the present purpose we adopt the action (2), which includes theories like Horndeski/generalized Galileon [31,32], beyond Horndeski (GLPV) [33] and low-energy Hořava gravity [4,34,35]; however, the EFT action has been generalized to include a wider range of theories [20], in particular extensions of Hořava gravity [26,36]. Now, let us use the Arnowitt-Deser-Misner formalism [37] and expand the line element around the flat FLRW background.…”
Section: Modifying General Relativitymentioning
confidence: 99%
See 1 more Smart Citation